2021
DOI: 10.1111/pbr.12961
|View full text |Cite
|
Sign up to set email alerts
|

Drought response QTLs in a Super Basmati × Azucena population by high‐density GBS‐based SNP linkage mapping

Abstract: Basmati rice is favoured for its grain type and aroma, but its production is vulnerable due to climate change and freshwater accessibility. Discovery and refinement of genomic regions conferring drought tolerance are needed to develop new drought tolerant Basmati varieties. Using Recombinant Inbred Lines (RILs) derived from a cross between drought-sensitive elite Basmati variety, 'Super Basmati', and droughttolerant japonica cultivar, 'Azucena', a linkage map was constructed with 862 highquality GBS-based SNP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…They are also the preferred regions for fine mapping and candidate gene identification ( Xie et al., 2008 ). It can introduce genes related to crop quality, yield, and resistance into recipient crops simultaneously, control the correlation between traits in stable “QTL hotspots” or “QTL clusters” of different traits, and regulate pleiotropy of various traits through different metabolic pathways ( Huang and Yan, 2019 ; Waheed et al., 2021 ). Numerous studies have shown that the phenomenon of “QTL hotspots” or “QTL clusters” are prevalent in a variety of crops, such as crested wheatgrass ( Yang et al., 2022 ), wheat ( Cui et al., 2016 ), and sorghum ( Mace et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…They are also the preferred regions for fine mapping and candidate gene identification ( Xie et al., 2008 ). It can introduce genes related to crop quality, yield, and resistance into recipient crops simultaneously, control the correlation between traits in stable “QTL hotspots” or “QTL clusters” of different traits, and regulate pleiotropy of various traits through different metabolic pathways ( Huang and Yan, 2019 ; Waheed et al., 2021 ). Numerous studies have shown that the phenomenon of “QTL hotspots” or “QTL clusters” are prevalent in a variety of crops, such as crested wheatgrass ( Yang et al., 2022 ), wheat ( Cui et al., 2016 ), and sorghum ( Mace et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of drought-tolerant genotypes may consider the targeted rice growth stage [65]. Screening under drought stress conditions allows selection of the drought-tolerant plants within each line.…”
Section: Breeding For Rice Drought Tolerancementioning
confidence: 99%
“…However, they did not conduct any formal analysis for aroma in these lines. Waheed et al [65] reported one QTL on chromosome 7 and another on chromosome 11 for shoot dry weight and water uptake under drought conditions in recombinant inbred lines (RILs) developed from a cross between Super Basmati, an aromatic variety, and Azucena, a drought-tolerant cultivar. Nevertheless, they did not determine the aroma status in these lines.…”
Section: Development Of Aromatic Drought-tolerant Rice Varietiesmentioning
confidence: 99%
“…The QTLs identi ed were thoroughly compared with previously identi ed QTLs for any colocalization using the Q-Taro (QTL Annotation Rice Online) database (Kulkarni et al, 2020). Cluster of QTLs governing various traits located within <30 cM (Waheed et al, 2021) on the linkage map were also reported.…”
Section: Linkage Map Construction and Qtl Mappingmentioning
confidence: 99%